Optical resolution and mechanism using enantioselective cellulose, sodium alginate and hydroxypropyl‐β‐cyclodextrin membranes. Issue 6 (19th April 2017) - Yuan, Li‐Ming; Ma, Wei; Xu, Mei; Zhao, Hui‐Lin; Li, Yuan‐Yuan; Wang, Rui‐Lin; Duan, Ai‐Hong; Ai, Ping; Chen, Xue‐Xian
Abstract: Chiral solid membranes of cellulose, sodium alginate, and hydroxypropyl‐β‐cyclodextrin were prepared for chiral dialysis separations. After optimizing the membrane material concentrations, the membrane preparation conditions and the feed concentrations, enantiomeric excesses of 89.1%, 42.6%, and 59.1% were obtained for mandelic acid on the cellulose membrane, p ‐hydroxy phenylglycine on the sodium alginate membrane, and p ‐hydroxy phenylglycine on the hydroxypropyl‐β‐cyclodextrin membrane, respectively. To study the optical resolution mechanism, chiral discrimination by membrane adsorption, solid phase extraction, membrane chromatography, high‐pressure liquid chromatography ultrafiltration were performed. All of the experimental results showed that the first adsorbed enantiomer was not the enantiomer that first permeated the membrane. The crystal structures of mandelic acid and p ‐hydroxy phenylglycine are the racematic compounds. We suggest that the chiral separation mechanism of the solid membrane is "adsorption – association – diffusion, " which is able to explain the optical resolution of the enantioselective membrane. This is also the first report in which solid membranes of sodium alginate and hydroxypropyl‐β‐cyclodextrin were used in the chiral separation of p ‐hydroxy phenylglycine. Abstract :